Mechanical and Tribological Properties of (AlCrNbSiTiMo)N High-Entropy Alloy Films Prepared Using Single Multiple-Element Powder Hot-Pressed Sintered Target and Their Practical Application in Nickel-Based Alloy Milling - Jeng-Haur Horng; Wen-Hsien Kao; Wei-Chen Lin; Ren-Hao Chang (Lubricants)
(AlCrNbSiTiMo)N high-entropy alloy films with different nitrogen contents were deposited on tungsten carbide substrates using a radio-frequency magnetron sputtering system. Two different types of targets were used in the sputtering process: a hot-pressing sintered AlCrNbSiTi target fabricated using a single powder containing multiple elements and a vacuum arc melting Mo target. The deposited films were denoted as RN0, RN33, RN43, RN50, and RN56, where RN indicates the nitrogen flow ratio relative to the total nitrogen and argon flow rate (RN = (N2/(N2 + Ar)) × 100%). The as-sputtered films were vacuum annealed, with the resulting films denoted as HRN0, HRN33, HRN43, HRN50, and HRN56, respectively. The effects of the nitrogen content on the composition, microstructure, mechanical properties, and tribological properties of the films, in both as-sputtered and annealed states, underwent thorough analysis. The RN0 and RN33 films displayed non-crystalline structures. However, with an increase in nitrogen content, the RN43, RN50, and RN56 films transitioned to FCC structures. Among the as-deposited films, the RN43 film exhibited the best mechanical and tribological properties. All of the annealed films, except for the HRN0 film, displayed an FCC structure. In addition, they all formed an MoO3 solid lubricating phase, which reduced the coefficient of friction and improved the anti-wear performance. The heat treatment HRN43 film displayed the supreme hardness, H/E ratio, and adhesion strength. It also demonstrated excellent thermal stability and the best wear resistance. As a result, in milling tests on Inconel 718, the RN43-coated tool demonstrated a significantly lower flank wear and notch wear, indicating an improved machining performance and extended tool life. Thus, the application of the RN43 film in aerospace manufacturing can effectively reduce the tool replacement cost.